THE ENTREPRENEUR'S BOOK OF ACTIONS : ESSENTIAL DAILY EXERCISES AND HABITS FOR BECOMING WEALTHIER, SMARTER, AND A MORE SUCCESSFUL ENTREPRENEUR - Power, Rhett (New York : McGraw-Hill Education, 2017)
Equal parts instruction and inspiration, The Entrepreneur's Book of Actions provides the tools you need to build a successful company by discarding old habits, thinking in a new way, and focusing your efforts on what's important. You'll learn how to manage your time, your employees, and your money and become the leader you need to be. In the end, you will minimize effort needed to complete basic tasks, freeing up more time for creative and innovative endeavors--absolutely necessary ingredients for succeeding in today's competitive landscape.
Includes index
Keywords: Success in business; Success; Entrepreneurship